Best Products with TOPSIS Method and Sales Forecasting with Weighted Moving Average - Mohamad Helmi Ilman Fahmi; Imam Husni Al Amin (Journal of Applied Informatics and Computing, 2020)
In a company engaged in the sale and purchase of products can not be separated from the calculation of profit or loss that is the main factor for the company's progress. However, in certain companies such as minimarkets and convenience stores, it is not easy to record company profits and losses. This of course requires a system that can help companies in determining sales strategies or at least a picture of sales in the future. Things that can be done to help these problems is to create a system that forecast sales or forecasting. One method that can be used to make sales forecasts is the wighted moving average method. However, due to the large number of products sold in minimarkets with different values, of course there must be other methods that can filter products so that forecasting can be more effective. One way to handle this is to use a product ranking system with the Techinique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The topsis method was chosen because the calculation is very detailed and structured, so that it can maximize the ranking value. By combining sales forecasts and product ranking is expected to create a system that can help companies in determining sales strategies in the future. Later this system is combined with the point of sale system to get accurate sales results. This system is designed using PHP and Javascript programming languages, then the database is stored in MySQL.